Powerful blockholders and CEO turnover - WEI, Chi Shen (Institutional Knowledge at Singapore Management University, 2017)
We identify the power of institutional blockholders to influence management using previous occurrences of forced CEO turnover at other firms in the blockholders’ overall portfolio. We create a “powerful blockholder linkage” measure that strongly predicts future forced CEO turnover. These effects are larger when “powerful” blockholders are more motivated to monitor and when they have had valuable monitoring experience. Moreover, firms with powerful blockholders display higher CEO turnover-performance sensitivity, pursue more value-increasing mergers, and have higher firm value. Overall, our results suggest that an identifiable group of powerful blockholders play an important role in corporate governance.